2002
DOI: 10.2355/isijinternational.42.803
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Heating and Soaking Stage Length of a Galvannealing Furnace.

Abstract: In order to produce galvannealead coatings, the hot-dip galvanized sheet enters a galvannealing furnace as soon as it emerges from the zinc bath. This furnace normally comprises three stages: a heating stage, a soaking stage and a cooling stage. The length of each stage varies from plant to plant and depend on several factors such as heating and cooling method and sometimes on the space available on the galvanizing line. As is well known the main objective of such furnace is to deliver an alloyed coating with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Recently, the concept of "processing window" [2][3][4][5][6] for the galvannealing process has been introduced. A processing window is essentially an area in a soaking temperature vs. line velocity plot within which the galvanealing cycle of a certain zinc coated steel sheet will result in a coating iron content between 10 and 11 mass%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the concept of "processing window" [2][3][4][5][6] for the galvannealing process has been introduced. A processing window is essentially an area in a soaking temperature vs. line velocity plot within which the galvanealing cycle of a certain zinc coated steel sheet will result in a coating iron content between 10 and 11 mass%.…”
mentioning
confidence: 99%
“…In a recent work, Faria and Rios 6) showed that the following equation is valid: (2) where x and y are the furnace soaking and heating length, respectively, as indicated in Fig. 1.…”
mentioning
confidence: 99%